KEANEKARAGAMAN JENIS PAKU-PAKUAN (Pteridophyta) TERESTRIAL DI LINGKUNGAN ARBORETUM SYLVA UNIVERSITAS TANJUNGPURA PONTIANAK - Wanira, Ayu; Prayogo, Hari; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2018)
This study aims to determine the diversity of terrestrial pteridophyta species (pteridophyta) at the University Arboretum Sylva Tanjungpura Pontianak. The objek of the study was to observe the types of terrestrial fern plants found in research plots based on where they grew. This research use survey method with double plot area is 10 x 5 meters, taken Â± 10 % of the area of the Arboretum Sylva environment ( 32 observation plots). The result showed that the number of fern plants obtained from the observation plots of 1 to 32 plot were 8 species of terrestrial nails belonging to 5 families with 1138 individuals, the type of nail found was Asplenium longissimum, Asplenium belangeri Bori, Lygodium circinatum SW, Angiospteris avecta Hoffm, Nephrolepis hirsutula Forst, Nephrolepis bisserata SW, Stenochleana palustris Burm, and Lygodium scandes L. The value of dominance Index (C) in the study site is low because the index value of dominance of all plots does not exceed the value of 1. This shows that the community does not find one or two dominant plant species that dominate in that location.Keywords: diversity, fern nail plant, terrestrial.